Revolutionizing Arabic Vocabulary Learning with Mimicry Memorization - Damayanti, Damayanti; Ammar, Farikh Marzuki (Universitas Muhammadiyah Sidoarjo, 2023)
This study investigates the effectiveness of the Mimicry Memorization method in improving Arabic vocabulary skills among fifth-grade students at Al Islam Elementary School Pehnangka Ngawi. Utilizing classroom action research across two cycles, the research demonstrates a significant enhancement in students' classical learning completeness, with a notable increase from 62.06% to 89.65%. Through pre-tests, post-tests, observation, and documentation, the study highlights the positive impact of the Mimicry Memorization method on student engagement, learning outcomes, and teacher effectiveness. These findings underscore the importance of innovative teaching methods in optimizing educational experiences and outcomes. Highlight: Implementation of Mimicry Memorization method significantly improves Arabic vocabulary skills. Classroom action research demonstrates a notable increase in students' learning completeness. Findings underscore the importance of innovative teaching methods for optimizing educational outcomes. Keywoard: Mimicry Memorization, Arabic vocabulary, Classroom action research, Learning outcomes, Student engagement